Emotional sounds in space: asymmetrical representation within early-stage auditory areas - Grisendi, Tiffany; Clarke, Stephanie; Da Costa, Sandra (Frontiers in Neuroscience, 2023)
Evidence from behavioral studies suggests that the spatial origin of sounds may influence the perception of emotional valence. Using 7T fMRI we have investigated the impact of the categories of sound (vocalizations; non-vocalizations), emotional valence (positive, neutral, negative) and spatial origin (left, center, right) on the encoding in early-stage auditory areas and in the voice area. The combination of these different characteristics resulted in a total of 18 conditions (2 categories x 3 valences x 3 lateralizations), which were presented in a pseudo-randomized order in blocks of 11 different sounds (of the same condition) in 12 distinct runs of 6 min. In addition, two localizers, i.e., tonotopy mapping; human vocalizations, were used to define regions of interest. A three-way repeated measure ANOVA on the BOLD responses revealed bilateral significant effects and interactions in the primary auditory cortex, the lateral early-stage auditory areas, and the voice area. Positive vocalizations presented on the left side yielded greater activity in the ipsilateral and contralateral primary auditory cortex than did neutral or negative vocalizations or any other stimuli at any of the three positions. Right, but not left area L3 responded more strongly to (i) positive vocalizations presented ipsi- or contralaterally than to neutral or negative vocalizations presented at the same positions; and (ii) to neutral than positive or negative non-vocalizations presented contralaterally. Furthermore, comparison with a previous study indicates that spatial cues may render emotional valence more salient within the early-stage auditory areas.